A Comparative Study Between Bhuddhacarita and Pathamasombodhi - Buddhacorn, Abhiwatchai (Academic MCU Buriram Journal, 2018)
The similarity of subject matters in Buddhacarita Canon and Pathamasombodhi canon was about birth, ordination, meditation, first sermon, Nirvana, funeral ceremony and distributing Buddha’s relics including main teaching of Buddha. As for people mentioned in canon was also same. Different matters in Buddhacarita Canon and Pathamasombodhi canon was about acknowledging Dhamma of Buddha and basic Dhamma principle used in declaring religion. In Buddhacarita Canon, it was a basic as for Pathamasombodhi canon, it used gradual instruction principle. Beside this, role and duty of Phra Uthayee was also different.